SARS-CoV-2 Omicron (B.1.1.529) Variant: No Time to Wait! - Rahmani, Shayan; Rezaei, Nima (Acta Biomedica Atenei Parmensis, 2022)
On November 26th, a new severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), B.1.1.529, was designated by the World Health Organization (WHO), named Omicron, and classified as a variant of concern (VOC). The news raised an international alarm about a new wave of coronavirus disease 2019 (Covid-19) outbreak, since Omicron has a large group of mutations which may affect the way it spread, cause disease, and escape from the immunity. Therefore, it is essential to take a closer look at how it has emerged, how it may sustain the pandemic, and how we can act correspondingly, both nationally and internationally, to help control the spreading of the disease.